Utility of measurement of left ventricular global longitudinal strain by two-dimensional speckle-tracking echocardiography to predict cardiovascular events in patients with left ventricular systolic dysfunction: A pilot study - Susheel Kumar Malani; Digvijay Nalawade; Sridevi Chigulapalli; Shubhangi Kanitkar; Ajitkumar Jadhav; Madhura Gandhi (Heart India)
Introduction: This pilot study explores whether left ventricular global longitudinal strain (LV GLS), measured by two-dimensional (2D) speckle-tracking echocardiography (STE), can predict cardiovascular events in patients with left ventricular systolic dysfunction (LVSD), including those with ischemic and nonischemic dilated cardiomyopathy, postvalve surgery, and chemotherapy recipients, compared to traditional parameters such as left ventricular ejection fraction (LVEF) and wall motion score index (WMSI). Materials and Methods: This retrospective study included 45 patients from a tertiary care center, with global longitudinal strain measurements taken between July 2022 and October 2023. Echocardiographic data, including LV-GLS, LVEF, and WMSI, were collected, alongside monitoring for cardiovascular events such as heart failure hospitalizations, cardiac mortality, and all-cause mortality. Results: In a study involving 45 patients (mean age: 57.9 years, 31.1% females), 17.8% experienced events. Patients with events exhibited significantly lower LV GLS values (P = 0.002), reduced LVEF (P = 0.002), and higher WMSI (P = 0.001). Mortality was higher in patients with LVEF <30% (62.5% vs. 18.9%, P = 0.026). Receiver operating characteristic analysis showed a significant area under the curves (AUCs) for LV GLS (0.846) and WMSI (0.860), while LVEF had a lower AUC (0.140). These findings suggest LV GLS and WMSI are valuable indicators for diagnosis and risk assessment, although more extensive studies are needed for validation. Conclusions: In this pilot study, LV GLS assessed through 2D STE shows promise as an effective predictor of cardiovascular events in LVSD, potentially surpassing traditional parameters. Further research and large samples are needed to validate its use in larger cohorts, offering a valuable addition to risk assessment in these patients.